Color-Pattern Evolution in Response to Environmental Stress in Butterflies - Hiyama, Atsuki; Taira, Wataru; Otaki, Joji M. (Frontiers in Genetics, 2012)
It is generally accepted that butterfly wing color patterns have ecological and behavioral functions that evolved through natural selection. However, particular wing color patterns may physiologically be produced in response to environmental stress without significant function. These patterns would represent an extreme expression of phenotypic plasticity and can eventually be fixed genetically in a population. Here, three such cases in butterflies are concisely reviewed and their possible mechanisms of genetic assimilation are discussed. First, certain modified color pattern of Vanessa indica induced by temperature treatments resembles the natural color patterns of its closely related species of the genus Vanessa (sensu stricto). Second, a different type of color-pattern modification can be induced in Vanessa cardui as a result of a general stress response, which is very similar to the natural color pattern of its sister species Vanessa kershawi. Third, a field observation was reported, together with experimental support, to show that the color-pattern diversity of a regional population of Zizeeria maha increased at the northern range margin of this species in response to temperature stress. In these three cases, modified color patterns are unlikely to have significant functions, and these cases suggest that phenotypic plasticity plays an important role in butterfly wing color-pattern evolution. A neutral or non-functional trait can be assimilated genetically if it is linked, like a parasitic trait, with another functional trait. In addition, it is possible that environmental stress causes epigenetic modifications of genes related to color patterns and that their transgenerational inheritance facilitates the process of genetic assimilation of a neutral or non-functional trait.